Post-SSRI Sexual Dysfunction: Clinical Characterization and Preliminary Assessment of Contributory Factors and Dose-Response Relationship. Issue 3 (June 2015) - Ben-Sheetrit, Joseph; Aizenberg, Dov; Csoka, Antonei B.; Weizman, Abraham; Hermesh, Haggai
Abstract : Abstract: Emerging evidence suggests that sexual dysfunction emerging during treatment with selective serotonin reuptake inhibitors (SSRIs) and/or serotonin-norepinephrine reuptake inhibitors (SNRIs) persists in some patients beyond drug discontinuation (post-SSRI sexual dysfunction [PSSD]). We sought to identify and characterize a series of such cases and explore possible explanatory factors and exposure-response relationship. Subjects who responded to an invitation in a forum dedicated to PSSD filled out a survey via online software. Case probability was defined according to the following 3 categories of increasing presumed likelihood of PSSD. Noncases did not meet the criteria for possible cases. Possible cases were subjects with normal pretreatment sexual function who first experienced sexual disturbances while using a single SSRI/SNRI, which did not resolve upon drug discontinuation for 1 month or longer as indicated by Arizona Sexual Experience Scale scores. High-probability cases were also younger than 50-year-olds; did not have confounding medical conditions, medications, or drug use; and had normal scores on the Hospital Anxiety and Depression Scale. Five hundred thirty-two (532) subjects completed the survey, among which 183 possible cases were identified, including 23 high-probability cases. Female sex, genital anesthesia, and depression predicted current sexual dysfunction severity, but dose/defined daily dose ratio and anxiety did not. Genital anesthesia did not correlate with depression or anxiety, but pleasureless orgasm was an independent predictor of both depression and case probability. Limitations of the study include retrospective design and selection and report biases that do not allow generalization or estimation of incidence. However, our findings add to previous reports and support the existence of PSSD, which may not be fully explained by alternative nonpharmacological factors related to sexual dysfunction, including depression and anxiety.